Efficiency Analysis of the Asymmetric 2-Level Outphasing PA with Rayleigh Enveloped Signals - Abou-Chahine, Zeid; Felgentreff, Tilman; Fischer, Georg; Weigel, Robert (IEEE Topical Conference on Power Amplifiers for Wireless and Radio Applications (PAWR), 2012)
This paper focuses on the analysis of the generalized asymmetric outphasing amplification, yielding an expression for its combining efficiency. It also briefly reviews the outphasing power amplifier (PA) concept and interprets it from a functional perspective. The paper concludes with an analytical efficiency optimization for the 2-level asymmetric case with the transmitted signal having a Rayleigh amplitude distribution.
elib2cris::1512001600,abou-chahine2012
Keywords: optimisation; power amplifiers; Rayleigh amplitude distribution; Rayleigh enveloped signals; asymmetric 2-level outphasing PA; efficiency analysis; efficiency optimization; generalized asymmetric outphasing amplification; outphasing power amplifier; Bandwidth; Microwave circuits; Microwave communication; Modulation; Optimization; Peak to average power ratio; Outphasing architecture; RF PA; Rayleigh PDF; Wilkinson power combining; efficiency maximization